Modelling the δ18O value of cave drip water and speleothem calcite - Wackerbarth, Anne Katrin; Scholz, D.; Fohlmeister, Jens; Mangini, Augusto (Earth and planetary science letters, 2010)
Stable isotope signals recorded in speleothems have provided important insights about past climate variability in recent years. Quantitative reconstruction of mean annual temperature and the amount of precipitation, however, remains difficult because the stable isotope signals are influenced by various processes. Here we present a drip water model, which shows how these climate parameters affect the oxygen isotope signal of cave drip water...
Im Titel erscheint die Zahl 18 hochgestellt
Gesehen am 19.09.2023